Argentina : Ex-Post Evaluation of Exceptional Access Under the 2018 Stand-By Arrangement-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
On June 20, 2018, the Executive Board approved the largest stand-by arrangement in the Fund's history, in support of Argentina's 2018-21 economic program. After an augmentation in October 2018, access under the arrangement amounted to USD 57 billion (1,227 percent of Argentina's IMF quota). The program saw only four of the planned twelve reviews completed, and did not fulfil the objectives of restoring confidence in fiscal and external viability while fostering economic growth. The arrangement was canceled on July 24, 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Argentina